Ethno pedagogy and conservation practices of the erai-erai dance in the Lematang Malay Community, Lahat District, South Sumatra Indonesia - Monika Artasia; Hartono Hartono; Deasylina da Ary (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2022)
Ethno pedagogy examines the interaction of pedagogical and cultural traditions as well as social and pedagogical processes and examines educational methods and solutions used by the Lematang people in Lahat District. This study aims to analyze the application of Ethno pedagogy in learning erai-erai dance. Art-based qualitative methods with an ethnopedagogical approach as a data collection strategy based on observation, interviews and document research. Several stages of the interview activities included interview planning, conducting interviews, recording interview data and activities after the interview, namely checking the validity of the data and making systematic data so that it was ready to be used as material for further analysis. Source triangulation techniques to check data accuracy and test the credibility of data from various sources, then to compare the results of interviews between informants who are directly or indirectly involved. The results of this study are the dissemination of erai-erai dance performances through a socialization process so that ethnopedagogical practices emerge in the community with various learning strategies for erai-erai dance practised by each social class with their respective roles, thus directly or indirectly creating ethnopedagogical practices. Then, a conservation strategy involving ethnopedagogical practices in erai-erai dance is implemented using social media. The discussion above shows the contribution of research, although, on the other hand, this research has many weaknesses